An evaluation of race based income discrimination in post apartheid South Africa - Khewana, Xolile (Department of Commercial Law, 2022)
The South African labour market has been characterised by income inequality, which emanates from past discrimination legacies. The wage gap between white workers and blacks have been marginally high. The same goes for the wage gap between males and females who find themselves performing equal value work in most cases. White workers continue to occupy high-level positions in an organisation with higher salaries disproportionately to black workers who generally occupy lower-level positions and with low-income earnings. The dawn of democracy brought a new government that has passed legislation and regulations aimed at reversing the ills of the past and achieving labour reforms and workplace equality. This paper evaluates progress as a result of such legislation and government policy provisions, particularly the Employment Equity Act. The study considers the provisions of section 6(4) of the EEA, which is aimed at race and gender pay income inequality, and the effects of section 27 of the EEA, which attempts to address disproportionate income differentials, by analysing data, and other observations and inputs from various sources. Based on the research and data, the findings point to the continued existence of wage differentials between races in South Africa. The conclusion is that the government's legislative intervention in the labour market through the Employment Equity Act has had a marginal economic impact on employees' wages and labour market transformation in the post-apartheid period. It is recommended that there is a need for a finetuned strategic approach to address both vertical and horizontal wage gap, further to this, the recommendations made by legislated bodies such as the Committee on Employment Equity need to be considered and implemented to achieve the goals as set up in the National Development Plan.